Liparis bomiensis (Orchidaceae, Epidendroideae, Malaxideae), a new species from Xizang, China - Ye, Chao; Ma, Chongbo; Jin, Xiaohua (Phytotaxa, 2024)
Liparis bomiensis, a new species of Orchidaceae from Bomi County, Linzhi, Xizang, China, is described and illustrated on morphological characters and molecular systematics. It is morphologically similar to L. rostrata with 2 thick projections at base of column, but differs from it by having purple and rhombic lip about 15 mm long, sepals and petals more than 15 mm long. Molecular phylogenetic results based on nuclear ribosomal ITS and plastid matK sequences showed that L. bomiensis is sister to L. glossula, but differs from it by having 2 thick nipple-like projections at base of column, two leaves, bracts triangular, column strongly curved. A detailed morphological description and photographic plates are provided for this new species.